Analyzing thousand years old game tigers and goats is still alive - Agarwal, Sakshi; Iida, Hiroyuki (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this research, the concept of Game Refinement Theory is applied to quantify the entertainment value of the game of TIGERS AND GOATS. This paper explores the game to get some compelling estimates of Game Refinement (GR) value of the game at various stages. The comparison of value is done for the two popular variants of the game. Also, we have compared the value with respect to the difficulty level of the game and the winning scenario. The results indicate that the game becomes more of a serious game with the increasing difficulty. The paper focuses on one main question - Why did we lose one of the game variants while the other one is still well sought-after and if there is any history behind this? After doing some research, we found that the game variant AADU PULI ATTAM which has lost its popularity has much lower game refinement value than the popular variant (BAGH CHAL). With this, we also present the hypothesis on their timeline that BAGH CHAL is an evolved version of AADU PULI ATTAM.